2020
DOI: 10.1029/2020gc009160
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐Mantle Anisotropy and Dynamics Beneath Northeast Asia: Insight From SKS and Local S Splitting Analysis

Abstract: Tectonics in Northeast Asia are characterized as the deep subduction of the Pacific Plate and the induced volcanism in Northeast China. Seismic anisotropy due to deformations is essential for understanding the mantle dynamics. However, the routine SKS splitting captures the accumulated seismic anisotropy from core‐mantle boundary to the surface, so the interpretation of the SKS splitting measurements is nonunique. Here, benefiting from abundant deep‐focus earthquakes in the subducting Pacific Plate, we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 61 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Previous SWS studies (Figure S8 in the Supporting Information ) show nearly NW‐SE FVDs under the Songliao basin (J. Li & Niu, 2010; Lu et al., 2020), and nearly E‐W FVDs under the North China basin (Y. Yang et al., 2018; T. Zheng et al., 2019; T. Zhu & Ma, 2021). Near the TLF, the FVDs are normal to the strike of the Tanlu fault (K. Liu et al., 2008; Z. Huang et al., 2011), which represent an integration of the NE‐SW anisotropy in the lithosphere and NW‐SE anisotropy in the asthenosphere (Bi et al., 2020). Beneath the North China basin, the FVDs change slightly at depths of 100–300 km (Figures 2c and S8 in the Supporting Information ), which may reflect the contribution of fossil anisotropy in the crust and/or lithosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous SWS studies (Figure S8 in the Supporting Information ) show nearly NW‐SE FVDs under the Songliao basin (J. Li & Niu, 2010; Lu et al., 2020), and nearly E‐W FVDs under the North China basin (Y. Yang et al., 2018; T. Zheng et al., 2019; T. Zhu & Ma, 2021). Near the TLF, the FVDs are normal to the strike of the Tanlu fault (K. Liu et al., 2008; Z. Huang et al., 2011), which represent an integration of the NE‐SW anisotropy in the lithosphere and NW‐SE anisotropy in the asthenosphere (Bi et al., 2020). Beneath the North China basin, the FVDs change slightly at depths of 100–300 km (Figures 2c and S8 in the Supporting Information ), which may reflect the contribution of fossil anisotropy in the crust and/or lithosphere.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al, 2011),. which represent an integration of the NE-SW anisotropy in the lithosphere and NW-SE anisotropy in the asthenosphere(Bi et al, 2020). Beneath the North China basin, the FVDs change slightly at depths of 100-300 km (Figures2c and S8in the Supporting Information S1), which may reflect the contribution of fossil anisotropy in the crust and/or lithosphere.…”
mentioning
confidence: 99%
“…The arc‐shaped LAB and the variations of Moho depth under the Changbaishan range are likely caused by the upwelling asthenosphere beneath the Changbaishan volcano related to the present Pacific subduction. The local NE‐SW FPDs beneath the TLFZ may reflect the lithospheric deformation accompanying the Dunhua‐Mishan fault zone (the eastern branch of the TLFZ) since the Mesozoic (Bi et al., 2020; C. Liu et al., 2018). The crustal FPD from the anisotropic Rayleigh wave tomographic results is also uniformly oriented in NE‐SW around the TLFZ, parallel to its strike trend (Fan et al., 2020).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…We argue that the upwelling of hot material from the deep mantle resulted in the change of the horizontal flow direction of the asthenosphere (Figure 4b) and thus induced the vertical seismic anisotropy that is undetectable for the steeply propagating SKS waves and would be ultimately featured as weak or nonsplittings (Li et al., 2021). Anisotropy investigation using over 20 years of seismic records showed that in this subduction region, a kind of convection flow associated with the BMW as deep as the MTZ might also contribute to the observed seismic anisotropy (Bi et al., 2020; G. R. Guo et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited back-azimuth distribution, it is hard to investigate the detailed variation of the fast polarization direction with event azimuth, which could provide clues on multi-layered anisotropy (Cherie et al, 2016;Li & Chen, 2006;Makeyeva et al, 1992). Although some complexity beneath a GSN station MDJ (44.617°N, 129.591°E) has been revealed using more than 20 years of waveform data (Bi et al, 2020;Guo et al, 2021), most previous measurements of shear wave splitting in NE China did not find apparent azimuthal variation of the splitting parameters at most of the permanent stations (Gao & Sun, 2021;Li & Niu, 2010;Lu et al, 2019). Therefore, it is reasonable to obtain a salient anisotropy feature beneath this dense and long profile, which could be used to diagnose the systematic variation of the anisotropy pattern in the mantle.…”
Section: Methodsmentioning
confidence: 99%